Safety and Cost Considerations during the Introduction Period of Laparoscopic Radical Hysterectomy - A. Anagnostopoulos; S. Mitra; B. Decruze; R. Macdonald; J. Kirwan (Hindawi Limited, 2017)
Objective. To compare the safety, efficacy, and direct cost during the introduction of laparoscopic radical hysterectomy within an enhanced recovery pathway. Methods. A 1 : 1 single centre retrospective case control study of 36 propensity matched pairs of patients receiving open or laparoscopic surgery for early cervical cancer. Results. There were no significant differences in the baseline characteristics of the two cohorts. Open surgery cohort had significantly higher intraoperative blood loss (189 versus 934 mL) and longer postoperative hospital stay (2.3 versus 4.1 days). Although no significant difference in the intraoperative or postoperative complications was found more urinary tract injuries were recorded in the laparoscopic cohort. Laparoscopic surgery had significantly longer duration (206 versus 159 minutes), lower lymph node harvest (12.6 versus 16.9), and slower bladder function recovery. The median direct hospital cost was £4850 for laparoscopic radical hysterectomy and £4400 for open surgery. Conclusions. Laparoscopic radical hysterectomy can be safely introduced in an enhanced recovery environment without significant increase in perioperative morbidity. The 10% higher direct hospital cost is not statistically significant and is expected to even out when indirect costs are included.